Establishing an integrated and coordinated end of life care service – working in partnership. Issue 2 (1st September 2011) - Heaps, Kate; Jones, Penny; Rattigan, Carla; Howsam, Alexis; Stokes, Jackie; Williams, Beth
Abstract : The Greenwich Care Partnership was established in November 2010 to develop and provide an integrated end of life care service for the residents of the London Borough of Greenwich. The service is provided by one NHS organisation and two charitable organisations working together to provide a seamless, responsive service for dying people at home. The service has initially been commissioned on a "test and learn" basis, to establish the potential risks, benefits and potential cost savings of providing such a comprehensive service based in the home. The service aims to: ▶ Provide planned and urgent care around the clock to people at the end of life ▶ Reduce admissions and length of stay for people who do not need or wish to be cared for in hospital ▶ Improve the quality of care provided, reducing duplication and the time that clinical staff spend on administrative tasks ▶ Provide support for the key worker and improve inter-professional communication 24 h a day ▶ Reduce unnecessary expenditure and allow investment in services which enhance patient experience and promote choice, dignity and control at the end of life ▶ Support informal carers before and after bereavement. Data will be presented as monitored against Key performance indicators of the project, this will demonstrate achievement of the aims, although the project remains in development on date of submission. Additionally, the presenter will reflect on the highs and lows of partnership working and make recommendations for others embarking on a similar venture. This presentation will provide information which will be of use to any organisation considering embarking on a partnership venture; this approach is likely to be much more common in the current political climate. As we try to increase quality and capacity for care at home, this service delivery model will be of increased interest.